OPTIMIZING TIME MANAGEMENT STRATEGIES FOR EFFECTIVE READING: A COMPREHENSIVE STUDY (Konferensiyalar | Conferences, 2024)
The article closely examines the various time-saving methods that can be employed to boost reading effectiveness. The extensive research offers an in-depth understanding of the methodologies that readers should apply to maximize their study time. As a result, people can attain faster reading paces, reading retention, and comprehension thus spend less time consumed in learning. For those who wish to enhance their culture of reading and get better grades or work better, this is a perfect guide.